1999
DOI: 10.1038/sj.bjp.0702272
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of amylin with calcitonin gene‐related peptide receptors in the microvasculature of the hamster cheek pouch in vivo

Abstract: 1 This study used intravital microscopy to investigate the receptors stimulated by amylin which shares around 50% sequence homology with the vasodilator calcitonin gene-related peptide (CGRP) in the hamster cheek pouch microvasculature in vivo. 2 Receptor agonists dilated arterioles (diameters 20 ± 40 mm). The 7log of the concentrations (+s.e.mean; n=8) causing 50% increase in arteriole diameter were: human bCGRP (10.8+0.3), human aCGRP (10.8+0.4), rat aCGRP (10.4+0.3). Rat amylin and the CGRP 2 receptor selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…As NECA was the most potent agonist, the response to this agonist in the presence of adenosine receptor antagonists was studied. Repeated control curves to NECA showed that there was no loss of response with time or after repeated administration (results not shown), as shown previously for adenosine and other vasodilators (Jackson, 1993, Hall & Brain, 1994, 1999). None of the antagonists altered the resting diameter of the blood vessels (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As NECA was the most potent agonist, the response to this agonist in the presence of adenosine receptor antagonists was studied. Repeated control curves to NECA showed that there was no loss of response with time or after repeated administration (results not shown), as shown previously for adenosine and other vasodilators (Jackson, 1993, Hall & Brain, 1994, 1999). None of the antagonists altered the resting diameter of the blood vessels (Fig.…”
Section: Resultssupporting
confidence: 86%
“…As in other studies (e.g. Jackson, 1993, Hall & Brain, 1994, 1999), no time‐dependent changes in sensitivity to the agonists was noted.…”
Section: Adenosine Receptor Antagonist Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…All CGRP family peptides exhibit cardiovascular actions, although relative potency differs among the members, CGRPOAMRAM2[amylin (Ando et al 1990, Charles et al 1997, Hall & Brain 1999, Fujisawa et al 2004. CGRP is a neuropeptide in the brain and periphery, which is released from axon terminals innervating the vascular smooth muscles (see Brain & Grant 2004 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Amylin has been shown to have both vasodilator 20 and anti-inflammatory 21 properties. It shares 50% homology with calcitonin gene related peptide, which is recognised to be raised in acute inflammatory states such as trauma, 8 sepsis (neonatal and adult), 9 and hypotensive shock.…”
Section: Discussionmentioning
confidence: 99%